Photochromic alkali metal doped carbon nitride material as well as preparation method and application thereof
By using ultrasonication and light in the preparation process of photochromic materials, photochromic alkali metal doped carbon nitride materials were successfully prepared, solving the problems of complex preparation and poor thermal stability of existing materials, and realizing the Application expansion and performance improvement in information storage.
Patent Information
- Application Number
- CN202411461288.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-14
AI Technical Summary
The preparation process of existing photochromic materials is complex, with problems of environmental pollution and poor thermal stability, especially in information storage applications.
The carbon nitride powder is added to the mixed solution composed of alkali metal hydroxide and hole sacrificial agent to obtain a carbon nitride dispersion, and the photochromicity is prepared by deoxygenation, light, centrifugation, cleaning and drying. alkali metal doped carbon nitride material.
The embedded control of alkali metal ions is realized, the application of photochromic materials in information storage is expanded, and the high temperature resistance and physical and chemical stability is good.
Smart Images

Figure CN119432361A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photochromic materials, and in particular relates to a photochromic alkali metal-doped carbon nitride material and a preparation method and application thereof. Background Art
[0002] Photochromic materials change color when exposed to a light source of a specific wavelength, and generally return to their original color after the light ends, that is, photochromism is generally reversible. Using this property, photochromic materials can be used as protective materials, anti-counterfeiting materials, information storage encryption materials, etc. Photochromic materials used in practical applications are mostly organic materials. Organic photochromic materials have a fast light response and can be improved in functionality by modifying groups. Organic photochromic materials still have many defects. Their preparation process is relatively complicated and requires the use of toxic organic substances for synthesis, which increases costs and causes environmental pollution. In addition, organic photochromic materials have poor thermal stability and fatigue resistance. These defects have seriously limited the application of organic photochromic materials in information storage. Graphite phase carbon nitride materials have the advantages of simple synthesis method, stable physical and chemical properties, strong thermal stability (carbon nitride can generally be obtained by calcining urea at about 500°C), strong modifiability and adjustable band gap. Alkali metal carbon nitride prepared by the molten salt method has photochromic properties and has been used to make photochromic PUF anti-counterfeiting labels, light-responsive rewritable paper, photosensitive smart glass, etc. However, the molten salt method still has certain dangers and uncertainties, and its preparation process cannot control the embedding area of alkali metal ions, which limits the application of alkali metal carbon nitride in information storage.
[0003] Therefore, it is an urgent problem for those skilled in the art to provide a preparation method that can effectively control the alkali metal ion embedding process and expand the application of photochromism of alkali metal carbon nitride. Summary of the invention
[0004] Purpose of the invention: The first purpose of the present invention is to provide a photochromic alkali metal-doped carbon nitride material. The second purpose of the present invention is to provide a method for preparing the above-mentioned photochromic alkali metal-doped carbon nitride material. The third purpose of the present invention is to provide an application of the above-mentioned photochromic alkali metal-doped carbon nitride material.
[0005] Technical solution: The preparation method of the photochromic alkali metal-doped carbon nitride material of the present invention comprises the following steps:
[0006] (1) adding carbon nitride powder to a mixed solution consisting of an alkali hydroxide and a vacancy sacrificial agent and subjecting the mixture to ultrasonic treatment to obtain a carbon nitride dispersion;
[0007] (2) After the carbon nitride dispersion is deoxygenated, it is subjected to light treatment, and then centrifuged, washed and dried to obtain a photochromic alkali metal-doped carbon nitride material.
[0008] Furthermore, in step (1), the preparation method of the carbon nitride powder is: calcining a carbon nitride precursor to obtain carbon nitride powder; wherein the carbon nitride precursor is urea; the calcination conditions are: a heating rate of 5-10°C / min, and calcination at 500-550°C for 1-4h.
[0009] Furthermore, in step (1), the usage ratio of the alkali metal hydroxide to the hole sacrificial agent is 0.01-8 g:50 mL, preferably 1.2-2.8 g:50 mL.
[0010] Furthermore, in step (1), the hole sacrificial agent is anhydrous methanol, and the alkali metal includes lithium, sodium, and potassium; the concentration of the carbon nitride powder in the dispersed solution is 1-10 mg / mL, preferably 1-2 mg / mL; and the conditions of the ultrasonic treatment are: the ultrasonic power is 25000-30000 Hz, and the ultrasonic time is 1-10 min.
[0011] Furthermore, in step (2), the deoxygenation step is as follows: introducing argon into the dispersion for 10-30 min at a flow rate of 200-500 sccm.
[0012] Furthermore, in step (2), the conditions for the light treatment are: the light source is a 300W xenon lamp, and the light power is 200-600mW / cm 2 , the illumination time is 10-90min, the stirring rate is 300-600r / min; the centrifugal conditions are: the centrifugal speed is 5000-7000r / min, and the centrifugal time is 3-5min; the drying conditions are: freezing with liquid nitrogen and drying in a freeze dryer for 24-48h.
[0013] The present invention also provides applications of the alkali metal-doped carbon nitride material and the photochromic alkali metal-doped carbon nitride material prepared by the preparation method in the fields of information encryption and information reading.
[0014] Furthermore, the steps of encrypting the information are:
[0015] (11) dispersing carbon nitride powder in an alcohol solvent by ultrasonication to obtain a dispersion, and then spraying the dispersion on a substrate material to form a carbon nitride film;
[0016] (12) The substrate material with the carbon nitride film is immersed in a mixed solution composed of an alkali metal hydroxide and a hole sacrificial agent, and deoxygenated in a sealed environment. Thereafter, a shading plate with encrypted information is placed directly above the substrate material, and then a light treatment is performed perpendicular to the shading plate. The carbon nitride in the illuminated area will become alkali metal-doped carbon nitride and undergo photochromism, and the encrypted information will be displayed on the substrate material, thereby obtaining a substrate material with encrypted information. After the substrate material is taken out, the encrypted information disappears under no light conditions, and the information encryption process is completed.
[0017] Furthermore, the information reading step is: placing the matrix material with the encrypted information in water and fully soaking it to remove residual impurities, then taking it out and placing it in a hole sacrificial agent, deoxygenating it in a sealed environment, and then irradiating it with light. After the end, the encrypted information is displayed, and the information reading is completed, wherein the immersion time is about 10-30 minutes, and the water is changed 3-5 times; the conditions of the irradiation treatment are: using a xenon lamp light source, the light intensity is 400-600mW / cm 2 , the lighting time is 5-10min.
[0018] Furthermore, in the process step (11), the alcohol solvent is anhydrous ethanol, the ultrasonic conditions are: ultrasonic power is 25000-35000 Hz, and ultrasonic time is 20-40 min; the mass concentration of carbon nitride powder in the dispersion is 0.5-10 mg / mL, preferably 1-2 mg / mL; the spraying parameters are: the vertical distance between the nozzle and the substrate material is 10-30 cm, the speed of the nozzle movement is 15-30 mm / s, and the spraying speed of the dispersion is 20-50 μL / min; in step (12), the substrate material is glass; the deoxygenation treatment conditions are: argon gas is introduced into the mixed solution, the argon gas flow rate is 200-500 sccm, and the argon gas introduction time is 10-30 min; the light treatment conditions are: using a xenon lamp light source, the light intensity is 400-600 mW / cm 2 , the lighting time is 20-60min.
[0019] Principle of the invention: Graphite phase carbon nitride is an n-type semiconductor. When excited by light, photogenerated electrons and photogenerated holes are simultaneously generated on the carbon nitride. Methanol is a commonly used hole sacrificial agent that can capture photogenerated holes in the system, which leads to the accumulation of photogenerated electrons on the carbon nitride. Due to the negative charge carried by the photogenerated electrons themselves, the ability of carbon nitride to attract cations is greatly enhanced. When the carbon nitride with a layered structure is exposed to light in an alkaline methanol solution (i.e., a mixed solution composed of alkali metal hydroxides and hole sacrificial agents), the large amount of negative charge on the carbon nitride will attract the alkali metal cations in the solution through the interlayer and embed into the pyridine nitrogen pocket composed of the triazine ring structure. The positive charge carried by these embedded alkali metal ions can be used to balance the negative charge of the photogenerated electrons, and finally complete a photoinduced electron-ion coupling embedding process. These alkali metal cations (Li + 、Na + , K + ) is embedded and fixed in carbon nitride through light, and induces the formation of electron trap states in carbon nitride, and affects the light absorption range of carbon nitride, so that it exhibits a photochromic effect. These embedded alkali metal ions make carbon nitride behave like a capacitor, and its reversible photochromism is also related to the charging and discharging of the capacitor, that is, it shows color in the charging state and fades in the discharging state. The photogenerated electrons generated by light cause the alkali metal-doped carbon nitride to change color, so that we can embed alkali metal ions in a specific area of the carbon nitride film by controlling the illumination area, so that the specific area undergoes photochromism, which can realize the writing of information. When exposed to air or left for a long time, the electrons in the carbon nitride will consume oxygen or recombine with holes, causing the carbon nitride to return to the discharge state. At this time, the pre-written information will disappear due to fading, thus completing the encryption of the information. When the carbon nitride film is illuminated again in pure methanol, methanol will capture the photogenerated holes, leaving only the photogenerated electrons, and the capacitor will return to the charging state, then the pre-written information will reappear, thus completing the reading of the encrypted information. In summary, the present invention utilizes the photochromic effect of graphite phase carbon nitride in alkaline methanol solution to prepare an alkali metal-doped carbon nitride with photochromic effect. This is also a new method for doping alkali metal ions in carbon nitride, and based on the photochromic effect of this alkali metal carbon nitride, a method for information writing, encryption and reading has been developed.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: (1) Compared with alkali metal carbon nitride prepared by the molten salt method, the present invention can control the embedding area of alkali metal ions by controlling light, thereby realizing the information writing, encryption and reading functions of alkali metal carbon nitride; (2) The thin film formed by the alkali metal carbon nitride of the present invention can still read the pre-written information after being heated at 200°C for 30 minutes, showing strong high temperature resistance; (3) The thin film formed by the alkali metal carbon nitride of the present invention can still read information after being placed for 2 months, showing strong physical and chemical stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Scanning electron microscope images of CN (Example 1), Li-CN (Example 3), Na-CN (Example 2), K-CN (Example 1), and Cs-CN (Comparative Example 1) prepared according to Examples 1 to 3 and Comparative Example 1;
[0022] Figure 2 Transmission electron micrographs of CN (Example 1), Li-CN (Example 3), Na-CN (Example 2), K-CN (Example 3), and Cs-CN (Comparative Example 1) prepared according to Examples 1 to 3 and Comparative Example 1;
[0023] Figure 3 The pictures are of carbon nitride in Examples 1 to 3 and Comparative Example 1 before and after irradiation in pure methanol and methanol solutions of lithium hydroxide (LiOH), sodium hydroxide (NaOH), potassium hydroxide (KOH), and cesium hydroxide (CsOH);
[0024] Figure 4 The pictures are of the color change of carbon nitride after being irradiated in KOH methanol solution in Example 7, Example 8 and Example 9;
[0025] Figure 5 The UV-visible absorption spectra of the alkali metal-doped carbon nitride and ordinary carbon nitride prepared in Examples 1 to 3 and Comparative Example 1;
[0026] Figure 6 The band gap diagrams of the alkali metal carbon nitride and common carbon nitride prepared in Examples 1 to 3 and Comparative Example 1; Figure 7 The X-ray diffraction patterns of the alkali metal carbon nitride and common carbon nitride prepared in Examples 1, 2, 3, and 4;
[0027] Figure 8 A process diagram of writing, encrypting (erasing), and reading information on a carbon nitride film according to the steps of Example 5;
[0028] Fig. 9The photo of the carbon nitride film with the QR code written thereon in Example 6 and the photo of the QR code information read thereon after heating at 200°C;
[0029] Fig.10 This is a photo of the carbon nitride film with the QR code written on it in Example 6 and a photo of the QR code information read after being stored for two months. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with the embodiments and drawings.
[0031] Embodiment 1: The preparation method of the photochromic alkali metal-doped carbon nitride material provided in this embodiment specifically comprises the following steps:
[0032] (1) Weigh 12 g of urea and add it to a covered crucible. Place the crucible in a muffle furnace and heat it at a heating rate of 5 °C / min. Calcinate at 520 °C for 2 h. After cooling, obtain about 1 g of yellow carbon nitride powder, named CN.
[0033] (2) weighing 2.8 g of potassium hydroxide and dissolving it in 50 mL of anhydrous methanol to obtain a potassium hydroxide methanol solution; weighing 100 mg of the carbon nitride powder in step (1) and adding it to the potassium hydroxide methanol solution, and ultrasonicating at 30,000 Hz for 3 min to obtain a carbon nitride dispersion;
[0034] (3) adding the carbon nitride dispersion prepared in step (2) into a sealed quartz reactor, and introducing argon gas for 15 min to remove dissolved oxygen, with an argon gas flow rate of 300 sccm;
[0035] (4) The carbon nitride dispersion from which oxygen has been removed in step (3) is subjected to light treatment, using a 300W xenon lamp as the light source and a light intensity of 550mW / cm 2 , the illumination time is 60min, and the stirring rate is 550r / min, at which time the photochromic effect of carbon nitride can be observed;
[0036] (5) The carbon nitride after the light irradiation reaction in step (4) is centrifuged and washed, and washed three times with water and alcohol respectively. The centrifugal speed is 5500r / min, and the centrifugal time is 3min. The washed sample is pre-frozen with liquid nitrogen and then placed in a freeze dryer. After freeze drying for 24h, alkali metal-doped carbon nitride with photochromic effect can be obtained, and the sample is named K-CN.
[0037] Example 2: Alkali metal-doped carbon nitride was prepared according to the method in Example 1, except that the alkaline methanol solution used was prepared by mixing 2 g of sodium hydroxide with 50 mL of anhydrous methanol. The alkali-doped carbon nitride finally obtained was named Na-CN.
[0038] Example 3: Alkali metal-doped carbon nitride was prepared according to the method in Example 1, except that the alkaline methanol solution used was prepared by mixing 1.2 g of lithium hydroxide with 50 mL of anhydrous methanol. The alkali-doped carbon nitride finally obtained was named Li-CN.
[0039] Comparative Example 1: Alkali metal-doped carbon nitride was prepared according to the method in Example 1, except that: (1) the alkaline methanol solution used was prepared by mixing 8.4 g of cesium hydroxide monohydrate with 50 mL of anhydrous methanol, and the final product was named Cs-CN. (2) Cs-CN did not have photochromic properties.
[0040] Embodiment 5: The method for using the photochromic alkali metal carbon nitride material provided in this embodiment for information encryption and reading specifically comprises the following steps:
[0041] (1) adding 50 mg of carbon nitride to 50 mL of anhydrous ethanol, and ultrasonically treating at 35000 Hz for 20 min to obtain a carbon nitride ethanol dispersion. The preparation method of carbon nitride is consistent with the preparation method in Example 1;
[0042] (2) spraying the carbon nitride ethanol dispersion in step (1) onto a 10 cm×10 cm glass substrate heated at 100° C. using a spray gun, so as to form a carbon nitride film on the glass substrate; wherein the vertical distance between the spray head and the substrate is 15 cm; the speed of the spray head movement is 20 mm / s; and the spraying speed of the dispersion is 30 μL / min;
[0043] (3) placing the carbon nitride film in step (2) into a transparent sealed container containing a 1 mol / L potassium hydroxide methanol solution (the ratio of potassium hydroxide to methanol is 2.8 g:50 mL) to obtain an experimental device; an injection port is provided on the top of the device, and argon gas is introduced through the injection port for 15 minutes to remove dissolved oxygen, and the argon gas flow rate is 300 sccm;
[0044] (4) Align the hollow shading plate with the word "SEU" on the experimental device prepared in step (3); use a xenon lamp to illuminate vertically with a light power of 600 mW / cm 2 The illumination time is 30 minutes. After the illumination is over, it can be observed that the SEU mark appears in the area of the carbon nitride film exposed to light, which means that the information writing process is completed;
[0045] (5) The carbon nitride film in step (4) is taken out of the experimental device and exposed to air. The SEU mark on the film disappears, and the information encryption process is completed.
[0046] (6) Soaking the carbon nitride film in step (5) in 500 mL of deionized water, changing the deionized water every 5 minutes, and after changing the water 5 times, re-placing the carbon nitride film in a transparent sealed container containing pure methanol to obtain an experimental device; an inlet is provided on the top of the device, and argon gas is introduced through the inlet for 15 minutes to remove dissolved oxygen, and the argon gas flow rate is 300 sccm;
[0047] (7) The experimental device in step (6) was illuminated using a xenon lamp with a vertical illumination power of 600 mW / cm 2 The illumination time is 1 min. After the illumination ends, it can be observed that the SEU words written in step (4) reappear on the carbon nitride film, which means that the reading process of the encrypted information is completed.
[0048] Example 6: The process of writing, encrypting and reading information on a carbon nitride film is performed according to the steps in Example 5, except that the hollow shading plate used is a shading plate with a hollow QR code pattern, and the QR code information is successfully written, encrypted and read on the carbon nitride film.
[0049] Example 7: Alkali metal-doped carbon nitride was prepared according to the method in Example 1, except that the illumination time was 10 min.
[0050] Example 8: Alkali metal-doped carbon nitride was prepared according to the method in Example 1, except that the illumination time was 30 min.
[0051] Example 9: Alkali metal-doped carbon nitride was prepared according to the method in Example 1, except that the light intensity was 200 mW / cm 2 .
[0052] Test results such as Figure 1-Figure 10 shown. Figure 1 The scanning electron microscope images (SEM) of CN (Example 1), Li-CN (Example 3), Na-CN (Example 2), K-CN (Example 1), and Cs-CN (Comparative Example 1) prepared according to Examples 1 to 3 and Comparative Example 1 are shown. CN has a layered structure formed by stacking flakes, and its surface is relatively smooth. In comparison, the surface morphology of Li-CN, Na-CN, K-CN and Cs-CN after the alkali methanol reaction appears rough, and there are more and smaller nanoparticles on the surface. This is more obvious on Li-CN, Na-CN and K-CN, indicating that the alkali metal ions have a certain etching effect on the surface of CN during the reaction.
[0053] Figure 2 For Figure 1Transmission electron microscope images (TEM) of the same CN (Example 1), Li-CN (Example 3), Na-CN (Example 2), K-CN (Example 1), and Cs-CN (Comparative Example 1). CN has a typical lamellar structure. Compared with CN, K-CN and Na-CN, the lamellae are thinner and smaller in size, and there is a more obvious curling in the edge area, which indicates that the alkali metal ions in the reaction process can change the morphology of CN and help the peeling of CN lamellae. The thickness of Li-CN is also thinner than that of CN. Thinner CN lamellae mean more reactive sites and better photoelectron transport performance, which is conducive to the photocatalytic reaction, and this corresponds to the improvement of CN catalytic performance in LiOH methanol, NaOH methanol, and KOH methanol. In addition, the morphology of Cs-CN has not changed compared with CN.
[0054] Figure 3 The pictures are of carbon nitride prepared according to Examples 1 to 3 and Comparative Example 1 before and after irradiation in pure methanol and lithium hydroxide (LiOH), sodium hydroxide (NaOH), potassium hydroxide (KOH), and cesium hydroxide (CsOH) methanol solutions. It can be found that the carbon nitride in pure methanol does not change color due to light, while the carbon nitride in LiOH methanol solution, NaOH methanol solution, and KOH methanol solution changes color after light, proving that carbon nitride materials with photochromic properties are produced during the reaction, and the degree of color change is LiOH methanol < NaOH methanol < KOH methanol. The carbon nitride in the CsOH methanol solution does not change color, and the carbon nitride does not have photochromic properties in it.
[0055] Figure 4 This is a picture of the color change of carbon nitride prepared according to Example 7, Example 8, and Example 9 after being exposed to KOH methanol solution. 2 Under the light intensity of 10min and 30min, K + Embedded in CN and produce photochromic phenomenon. At 200mW / cm 2 Illumination for 60 min at a light intensity of can also cause CN in KOH methanol solution to produce photochromic phenomenon.
[0056] Figure 5 The UV-visible light absorption spectra of the alkali metal-doped carbon nitride and the ordinary carbon nitride prepared in Example 1 to Example 3 are shown in Table 1. The light absorption performance of the potassium ion-doped carbon nitride prepared in Example 1 is significantly improved after illumination.
[0057] Figure 6The band gaps of the alkali metal-doped carbon nitride and the ordinary carbon nitride prepared in Examples 1 to 3 and Comparative Example 1 are shown in Figure 1. The band gaps of the samples are CN: 2.62eV, Li-CN: 2.56eV, Na-CN: 2.52eV, K-CN: 2.16eV, and Cs-CN: 2.64eV. The band gap of K-CN changes significantly, and its photochromic performance is also the best.
[0058] Figure 7 The X-ray diffraction patterns (XRD) of the alkali metal-doped carbon nitride and the ordinary carbon nitride prepared in Examples 1 to 3 and Comparative Example 1 are shown in Table 1. The peaks representing the layered structure of carbon nitride (CN) between 25° and 30° of Na-CN (Example 2) and K-CN (Example 1) are significantly shifted to the right, indicating that K + with Na + CN is embedded.
[0059] Figure 8 This is a flow chart of Example 5, which is mainly divided into three processes: writing information, erasing information, and reading information. Writing information: The CN film in the KOH methanol solution is illuminated through a light shield with information, and the corresponding information can be written. Erasing information: Contact with air will cause the information to disappear. Reading information: The CN film with information written on it is illuminated again, and the pre-written information can be read.
[0060] Fig. 9 This is the result of a heating experiment on the CN film with the two-dimensional code information written thereon in Example 6. After heating at 200° C. for 30 minutes, the two-dimensional code information can still be read.
[0061] Fig.10 This is the stability test result of the CN film with the two-dimensional code information written in Example 6. After being placed in the air for 2 months, the corresponding information can still be read.
Claims
1. A method for preparing a photochromic alkali metal-doped carbon nitride material, characterized in that: The following steps are involved: (1) adding carbon nitride powder to a mixed solution consisting of an alkali hydroxide and a vacancy sacrificial agent and subjecting the mixture to ultrasonic treatment to obtain a carbon nitride dispersion; (2) After the carbon nitride dispersion is deoxygenated, it is subjected to light treatment, and then centrifuged, washed and dried to obtain a photochromic alkali metal-doped carbon nitride material.
2. The preparation method according to claim 1, characterized in that: In step (1), the usage ratio of the alkali metal hydroxide and the hole sacrificial agent is 0.01-8g:50mL.
3. The preparation method according to claim 1, characterized in that: In step (1), the hole sacrificial agent is anhydrous methanol, the alkali metal includes lithium, sodium, and potassium; and the concentration of the carbon nitride powder in the dispersed solution is 0.5-10 mg / mL.
4. The preparation method according to claim 1, characterized in that: In step (2), the deoxygenation treatment step is: introducing argon gas into the dispersion liquid, the time of introducing argon gas is 10-30 minutes, and the argon gas flow rate is 200-500sccm.
5. The preparation method according to claim 1, characterized in that: In step (2), the conditions for the light treatment are: the light source is a 300W xenon lamp, and the light power is 200-600mW / cm 2 , illumination time is 10-90min, and stirring rate is 300-600r / min.
6. A photochromic alkali metal-doped carbon nitride material prepared by the preparation method according to claim 1.
7. Use of the photochromic alkali metal-doped carbon nitride material according to claim 6 in the field of information encryption and information reading.
8. The use according to claim 7, characterized in that: The steps of information encryption are: (11) dispersing carbon nitride powder in an alcohol solvent by ultrasonication to obtain a dispersion, and then spraying the dispersion on a substrate material to form a carbon nitride film; (12) The substrate material having the carbon nitride film is immersed in a mixed solution consisting of an alkali metal hydroxide and a hole sacrificial agent, and deoxygenated in a sealed environment. Thereafter, a shading plate with encrypted information is placed directly above the substrate material, and then a light treatment is performed perpendicular to the shading plate. The carbon nitride in the illuminated area will become alkali metal-doped carbon nitride and undergo photochromism, and the encrypted information will be displayed on the substrate material, thereby obtaining the substrate material with encrypted information. After the substrate material is taken out, the encrypted information disappears in the absence of light, and the information encryption process is completed.
9. The use according to claim 8, characterized in that: The steps of information reading are: placing the matrix material with encrypted information in water and fully soaking it to remove residual impurities, then taking it out and placing it in a hole sacrificial agent, performing deoxygenation treatment in a sealed environment, and then performing light treatment. After the end, the encrypted information is displayed, and the information reading is completed.
10. The use according to claim 8, characterized in that: In step (11), the spraying parameters are: the vertical distance between the nozzle and the substrate material is 10-30 cm, the speed of the nozzle movement is 15-30 mm / s, and the spraying speed of the dispersion is 20-50 μL / min.